1992
DOI: 10.1007/bf02245509
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine decreases self-control in rats: a preliminary report

Abstract: Cocaine abuse is often associated with behavior that takes into account short-term, but not long-term consequences. However, there has been no empirical research concerning the effects of cocaine on self-control (choice of a larger, more delayed reinforcer over a smaller, less delayed reinforcer). In the present research, when food-deprived rats repeatedly chose between a larger, more delayed food reinforcer and a smaller, less delayed food reinforcer, chronic intraperitoneal injections of 15 mg/kg cocaine (bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 11 publications
9
58
0
Order By: Relevance
“…Similar to 5-HT depletion, amphetamine administration increases impulsive, premature responding on the 5CSRTT in a DA-dependent fashion (Cole and Robbins, 1987;Harrison et al, 1999;Van Gaalen et al, 2006)Fthis is another instance of the overall involvement of DA in behavioral activation with which this article began. However, effects of DA-enhancing psychostimulants on intertemporal choice have varied, with some studies reporting that they promote choice of delayed reinforcers (Wade et al, 2000;de Wit et al, 2002), consistent with its beneficial effect on clinical impulsivity in ADHD, whereas others have found the opposite effect (Logue et al, 1992;Charrier and Thiebot, 1996;Evenden and Ryan, 1999). Only the latter set of findings is consistent with the model presented here.…”
Section: Intertemporal Choicesupporting
confidence: 86%
“…Similar to 5-HT depletion, amphetamine administration increases impulsive, premature responding on the 5CSRTT in a DA-dependent fashion (Cole and Robbins, 1987;Harrison et al, 1999;Van Gaalen et al, 2006)Fthis is another instance of the overall involvement of DA in behavioral activation with which this article began. However, effects of DA-enhancing psychostimulants on intertemporal choice have varied, with some studies reporting that they promote choice of delayed reinforcers (Wade et al, 2000;de Wit et al, 2002), consistent with its beneficial effect on clinical impulsivity in ADHD, whereas others have found the opposite effect (Logue et al, 1992;Charrier and Thiebot, 1996;Evenden and Ryan, 1999). Only the latter set of findings is consistent with the model presented here.…”
Section: Intertemporal Choicesupporting
confidence: 86%
“…In fact, the effects of acute administration of psychostimulants on laboratory models of impulsive choice have varied. Some studies have found that they promote choice of delayed reinforcers Richards, Chock, Carlson, de Wit, & Seiden, 1997;Richards, Sabol, & de Wit, 1999;Sagvolden et al, 1992;Wade, de Wit, & Richards, 2000), while others have found the opposite effect (Charrier & Thiébot, 1996;Evenden & Ryan, 1996;Logue et al, 1992); the same psychostimulant can even have opposite effects in different tasks designed to measure impulsivity (Richards, Chock, et al, 1997). One factor that may explain some of these discrepant effects is the presence of cues or signals present during the delay to the larger/later alternative.…”
Section: Psychostimulants and Impulsivitymentioning
confidence: 99%
“…This suggests that the effects of dopaminergic drugs on impulsivity depend on the presence or absence of conditioned cues. Other investigators (e.g., Logue et al 1992;Evenden and Ryan 1996;Charrier and Thiebot 1996) have found that acute doses of stimulant drugs increase impulsivity on delay discounting procedures. The procedural differences that account for these varying results across the studies have yet to be identified.…”
mentioning
confidence: 94%